PERANCANGAN APLIKASI PENJUALAN BERBASIS WEB PADA PT CAHAYA DESAIN INDONESIA - Daffa Salsabila; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This study aims to design and develop a web-based sales application for PT Cahaya Desain Indonesia to create a more structured and efficient sales process. The application facilitates customer access to product information, allows for easy ordering, and provides updates on available products. System development follows the Systems Development Life Cycle (SDLC) methodology with a Waterfall approach, encompassing planning, analysis, design, implementation, and maintenance phases. Technologies used include MySQL as the database to store and manage product and transaction data, with HTML and PHP serving as the main programming languages to build the application`s interface and functionality. The application is intended to improve the company's operational efficiency and make it easier for customers to search for and purchase the products they need.